1994
DOI: 10.1136/bmj.309.6961.1054
|View full text |Cite
|
Sign up to set email alerts
|

Relation between socioeconomic deprivation and pathological prognostic factors in women with breast cancer

Abstract: figure).Since significant differences in survival were observed across all age groups, they were unlikely to be due to excess deaths from other causes among deprived women. There appeared to be four possible explanations for the differences between socioeconomic groups: differences in tumour stage, tumour biology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
1
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 17 publications
5
53
1
2
Order By: Relevance
“…However, several studies have shown deprived women to have poorer survival from breast cancer. Previous work carried out by the authors (Macleod et al, 2000a) confirmed earlier research (Carnon et al, 1994;Schrijvers et al, 1995) in showing no relationship between deprivation and pathological prognostic factors in women with early breast cancer. In addition, we have shown (Macleod et al, 2000b) that the NHS delivered health care equitably to women with breast cancer who lived in affluent and deprived areas.…”
supporting
confidence: 69%
“…However, several studies have shown deprived women to have poorer survival from breast cancer. Previous work carried out by the authors (Macleod et al, 2000a) confirmed earlier research (Carnon et al, 1994;Schrijvers et al, 1995) in showing no relationship between deprivation and pathological prognostic factors in women with early breast cancer. In addition, we have shown (Macleod et al, 2000b) that the NHS delivered health care equitably to women with breast cancer who lived in affluent and deprived areas.…”
supporting
confidence: 69%
“…Part of this difference is explained by more oestrogen receptor (ER) negative tumours in deprived women, but no other pathological differences have been observed . Several other studies have looked at other pathological criteria as the reason for the persistent survival differences and they have all failed to demonstrate an association (Carnon et al, 1994;Macleod et al, 2000a;Brewster et al, 2001). Access to health services does not appear to be a factor; in fact, deprived women appear to use primary care resources more often than the more affluent (Macleod et al, 2000b).…”
mentioning
confidence: 99%
“…3 To date, the reasons for social disparities in breast cancer prognosis are far from being established. Possible explanations include differences in sector of care, 7,8 access to early diagnosis, stage at diagnosis, 9 tumor biology 10,11 such as estrogen receptor status, [10][11][12][13] grade 9,13,14 or histologic type 13 and access to optimal treatment. 10,13,15 However, despite the numerous publications on social or ethnical disparities in breast cancer outcome, we still do not know to which extent these factors explain social inequalities in breast cancer prognosis.…”
mentioning
confidence: 99%